2021
DOI: 10.3390/ijerph18115750
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Neuropsychological Performance between Refugee and Non-Refugee Children in Palestine

Abstract: Neuropsychological studies on refugee children are scarce, but there are even less in the case of Palestinian children. This work aims to study the neuropsychological performance of Palestinian refugee children in Palestine compared to other Palestinian children living outside refugee camps. A comprehensive Neuropsychological battery was administrated to 584 Palestinian school children (464 refugees and 120 non-refugees) aged 6, 7, and 8 years old. Results showed that non-refugee children outperformed refugee … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Additionally, a prospective cohort study showcased increasing depressive symptoms are a risk factor dementia ( 19 ). While the literature on dementia risk and cognitive decline among Arab refugees is severely lacking, a study of Palestinian children found that non-refugee children outperformed refugee children in sustained attention, verbal memory, and visual memory ( 44 ). It is evident from the results of this study that many participants reported depressive symptoms and/or described PTSD symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a prospective cohort study showcased increasing depressive symptoms are a risk factor dementia ( 19 ). While the literature on dementia risk and cognitive decline among Arab refugees is severely lacking, a study of Palestinian children found that non-refugee children outperformed refugee children in sustained attention, verbal memory, and visual memory ( 44 ). It is evident from the results of this study that many participants reported depressive symptoms and/or described PTSD symptoms.…”
Section: Discussionmentioning
confidence: 99%